2022
DOI: 10.1108/jeim-10-2021-0442
|View full text |Cite
|
Sign up to set email alerts
|

The role of enterprise information systems strategies enabled strategy-making on organizational innovativeness: a resource orchestration perspective

Abstract: PurposeThe paper aims to establish the role of enterprise information systems strategies (ISS) enabled by business strategies for attaining organizational innovativeness (ORIN) mediated by performance (decision-making and business processes) under environmental turbulence.Design/methodology/approachThe research framework is developed based on theoretical grounding and validated with the help of 408 responses from Brazil using SmartPLS path modeling.FindingsThe results of the research suggest that the resource … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(32 citation statements)
references
References 65 publications
0
32
0
Order By: Relevance
“…Finally, insights resulting from the BIA operation can support decision-making in an organisation-wide level. These results are accomplished through the construction of corporate culture that encourages the attainment of BIA indicators and goals and incorporates an analytical decision-making orientation (Akter et al ., 2016; Yang et al ., 2020; Liu et al ., 2022; Wamba, 2022; Yoshikuni and Dwivedi, 2023), data-driven culture and organisational learning (Wamba et al ., 2017; Behl et al ., 2019; Fosso Wamba et al ., 2020; Nguyen et al ., 2022b), and technical infrastructures (Chen et al ., 2015; Duan et al ., 2019; Wang et al ., 2023). A rational integration of these factors within the overarching purpose of BIA implementation can trigger an inclusive organisational context where insights from the BIA system can be fully supported and encouraged (Alshamaila et al ., 2013; Maroufkhani et al ., 2020).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, insights resulting from the BIA operation can support decision-making in an organisation-wide level. These results are accomplished through the construction of corporate culture that encourages the attainment of BIA indicators and goals and incorporates an analytical decision-making orientation (Akter et al ., 2016; Yang et al ., 2020; Liu et al ., 2022; Wamba, 2022; Yoshikuni and Dwivedi, 2023), data-driven culture and organisational learning (Wamba et al ., 2017; Behl et al ., 2019; Fosso Wamba et al ., 2020; Nguyen et al ., 2022b), and technical infrastructures (Chen et al ., 2015; Duan et al ., 2019; Wang et al ., 2023). A rational integration of these factors within the overarching purpose of BIA implementation can trigger an inclusive organisational context where insights from the BIA system can be fully supported and encouraged (Alshamaila et al ., 2013; Maroufkhani et al ., 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Management capability and clear motivations and goals for BIA adoption have been considered as being significant determinants that directly influence MSMEs' BIA implementation. The readiness for BIA adoption in an organisation can be illustrated through a clear motivation and clear development goals, aiming to adopt the new technological applications and systems (Gangwar, 2018;Yoshikuni and Dwivedi, 2023). These determinants represent an organisation's capability to manage and exploit available resources including IT and managerial capability towards the successful adoption of new technologies for a particular purpose (Fosso Wamba et al, 2020;Wamba, 2022).…”
Section: Management Capabilitymentioning
confidence: 99%
“…Liu et al (2023) analyzed the relationship between digital platform capabilities and corporate innovation strategies from the perspective of strategic information management. Yoshikuni and Dwivedi (2023) demonstrated the role of digital technologies in developing an overarching business strategy to achieve organizational innovation. Specifically, as Birkinshaw and Gupta (2013) and Liang et al (2022) have suggested, instead of seeing DT exploitation and DT exploration as two poles on a continuum, we might better treat them as two dimensions of a business strategy.…”
Section: Discussionmentioning
confidence: 99%
“…Digital technologies no longer merely play a subservient or supportive role in organizational functions but have become an integral part of strategizing (Marabelli and Galliers, 2017; Morton et al ., 2022; Zhu et al ., 2022). DT in its own right can lead and enable business strategy by generating new business opportunities and exposing firms to novel markets in the digital era (Chen et al ., 2010; Vial, 2019; Verhoef et al ., 2021; Ilmudeen et al ., 2019; Yoshikuni and Dwivedi, 2023). Therefore, firms gradually shift the concentration from exploitation to exploration in the DT process (Teubner and Stockhinger, 2020), with the trade-off effects and contradictions of ambidexterity being mitigated in the new business landscape (Li et al ., 2017; Svahn et al ., 2017).…”
Section: Literature Review and Theory Developmentmentioning
confidence: 99%
“…This effort has not yet been undertaken, so our proposal of a specific mechanism for the relationship between DPC and TI from a resource perspective can provide new insights for theory and practice (Broekhuizen et al, 2021;Cenamor et al, 2019). What is more, it is difficult to simply rely on strategic information resources to achieve the expected innovation objectives under the dual impact of the current market and technological turmoil because of the lack of necessary intelligent analysis process Irani, 2002;Yoshikuni and Dwivedi, 2022). Saldanha et al (2017) also pointed out that even in the face of environmental uncertainty, the information processing process based on strategic objectives may help enterprises to find the direction of innovation.…”
Section: Introductionmentioning
confidence: 99%